Just and Lasting Change : When Communities Own Their Futures - Taylor, Carl E.; Taylor, Daniel C. (Book collections on Project MUSE., 2016)
With contributions from leading international experts in community-based development and public health, Just and Lasting Change offers a hopeful description of how people have made a difference in diverse communities around the world and a practical, accessible handbook for those trying to improve the quality of life in underdeveloped communities everywhere.